Physicochemical and Microbiological Quality of Buffalo Meat Patty with the Addition of Fenugreek Seed (Trigonella foenum graecum) During Storage Time - Harapin Hafid; Peni Patriani (Faculty of Animal Science Universitas Brawijaya, 2023)
Buffalo meat has a good nutritional profile for the development of processed livestock products to meet consumer demand. For some reason, buffalo meat is less desirable to consumers because of its dark colour, coarser fibres, and tougher texture. Innovative product development is necessary as consumer demand tends to shift to ready-to-eat products. Processing buffalo meat into patties is an innovation in product development. Quality products require beneficial ingredients. Fenugreek seeds (Trigonella foenum-graecum) are herbal spices that are beneficial for health, contain protein, fibre, stabilizers, and emulsifiers, and have the potential for product development. The purpose of this study was to determine the effects of anise seed addition on the characteristics of buffalo meat patties. This study used a factorial Complete Randomized Design (4x2) with 4 replications. The factor I was the addition of fenugreek powder, F0 = control or 0%, buffalo meat patty dough + (F1 = 3% fenugreek powder; F2 = 6% fenugreek powder; F3 = 9% fenugreek powder). Factor 2 had a storage time of D1 = 30 days and D2 = 60 days.